Hotel performance and research streams: a network cluster analysis; International Journal of Contemporary Hospitality Management; Vol. 10 - Sainaghi R. Ruggero; Baggio R. Rodolfo; Phillips P. Paul; Mauri A. Aurelio (2018, 2018)
Title screen